Perancangan Konverter Boost Kuadratik Pada Solar Panel Menggunakan Kontrol PID - Anugrah Prasetyo Sutrisno; RB. Moch. Gozali; Widjonarko (FORTEI Regional VII Jawa Timur, 2022)
Using solar energy as a source of electricity has great potential. A boost converter is needed to overcome the low energy conversion efficiency of solar panels. Many boost converters have been used to achieve high efficiency, one of which is the quadratic boost converter. This study aims to increase the efficiency of solar panel output at low inputs. An overall study of the system with a lamp load of 2 volts from 09.00 WIB to 15.00 WIB showed that the highest efficiency was achieved at 10.15 am at 99% with an average efficiency of 80%. At the same time, the output voltage is 24.64 volts. From the voltage and current obtained simultaneously, the input power is 2.99 watts and the output power is 2.97 watts. From the tests I did, it appears that the quadratic boost converter can provide a fairly high output voltage. Low-duty cycles have been shown to produce higher output voltages than traditional boost converters.